Estudio de tiempos y movimientos para estandarizar el proceso productivo en el área de laminas prensadas de la empresa induce del Ecuador 2016 - Cangui Yugsi, Wilson Javier (2016)
The goal research was to improve production times, eliminate unnecessary movements, recognize bottlenecks, production machines redistribution, increase production quality, and establish a standard time to develop the pressed sheets production at INDUCE DEL ECUADOR COMPANY. There was found obstruction in the halls, the company is in working condition unsuitable and this doesn’t help the worker’s performance. In addition, there is not working time coordination in the pressing area, which is why the idea of the study of production processes that lead to have a process more efficient pressing which support to reach a better control production. The main goal of this proposal is to establish and standardize times and movements in each operation and thereby achieve increased productivity in the line of pressed sheets, the results generated by the time and motion study in the company determine a standard method work to meet production time optimizing its installed capacity to reach and meet the demand of nationwide customers.